Capital adequacy ratio analysis of top 10 clients (PCBs) of Citibank N.A. Bangladesh - Promi, Musharrat Hasan (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.